Associations between postpartum pain type, pain intensity and opioid use in patients with and without opioid use disorder: a cross-sectional study. (January 2023) - Lim, Grace; LaSorda, Kelsea R.; Krans, Elizabeth; Rosario, Bedda L.; Wong, Cynthia A.; Caritis, Steve
Abstract: Background: Pain is a multidimensional construct. The purpose of this cross-sectional, single-centre study was to evaluate the relationship between postpartum pain type with pain intensity and opioid use in people with and without opioid use disorder (OUD). Methods: Postpartum pain type was coded from McGill Pain Questionnaire and Patient-Reported Outcome Measurement Information System (PROMIS) inventories in people with or without OUD after childbirth in a 4-month period. The co-primary outcomes were pain intensity (0–10 scale) and total inpatient oxycodone (mg). Multivariable linear mixed-effects models assessed between- and within-person relationships for pain type (primary predictor) and outcomes. Results: There were 44 522 unique pain scores and types from 2610 people. Pain types were associated with pain intensity ( P <0.001). Between-person comparisons showed affective pain was associated with a small but higher total oxycodone dose (difference 1.04 mg compared with no affective pain, P <0.001). Among people with OUD, within-person comparisons showed that the presence of affective pain resulted in pain scores 1 point higher than when affective pain was not present ( P =0.002); between-person comparisons showed that people with affective pain had pain scores 6 points higher ( P =0.048). Within-person and between-person comparisons among OUD showed that nociceptive/neuropathic pain was associated with a higher total oxycodone dose (1.6 and 11.4 mg, respectively). Conclusions: Postpartum pain type was associated with pain intensity and opioid use. Further research is required to address the multiple dimensions of postpartum pain in people with and without OUD to improve treatment of postpartum pain.